Application of the DPSIR framework to assess environmental issues with an emphasis on waste management driven by stationary tourism in Adriatic Croatia - Mira Zovko; Sara Melkić; Izidora Marković Vukadin (Geoadria, 2021)
The complexity of the tourism sector relies on a variety of economic and social activities. Consequently, those are drivers that result in a variety of pressures and impacts on the environment. In order to track the progress towards sustainable tourism management, continuous data monitoring and a comprehensive assessment framework, such as the DPSIR - Driver-Pressure-State-Impact-Response, are a fundamental prerequisite. Among the environmental challenges within the DPSIR framework, municipal waste generated by the Croatian tourist industry is identified as one of the major environmental issues. In this research, evidence-based analysis using selected indicators within DPSIR framework was carried out with the emphasis on sustainable waste management. This holistic approach ensures a sound evaluation and adequate measures as a social response to address the main environmental issues regarding tourism intensity in the long term. In addition, the authors explored possible directions of more sustainable waste management in tourism for the Adriatic region of Croatia, considering the examples of the good practices implemented on the Island of Krk. Research and evaluation of selected indicators confirmed that tourism seasonality has an impact on the environment and revealed that high tourism intensity has a direct impact on the waste management infrastructure that is mostly established for a limited number of residents. Therefore, the authors suggest moderate tourism intensity as the most favourable option, resulting in a more sustainable waste management options, which produces less environmental pressure on the waste management infrastructure and the environment. Finally, through the research a new indicator was created, which explores sustainability of municipal waste management.